Conocimiento de la educación, decisiones pedagógicas y decisiones de política educativa - Touriñán López, José Manuel (Teoría de la Educación. Revista Interuniversitaria, 2009)
This article is engaged in upholding the appropiate place for decision in Educational Politics and Policy. All that inside the knowledge of Education. Political decision making in the educational arena has got a place between technical decisions and moral decisions. The one has increased its relevance in educational forum. On the other point of view, this kind of decision must not be understood as a result of the discipline «Politics of Education» or as a consequence of practical theories which are known like «Politica Pedagógica» (Pedagogy into Politics). Decisions in educational policy apply knowledge of Education but they are not made only with pedagogical facts and technical decisions. It’s posible to think of technical decisions as the ones which come not only from the process, but from the knowledge of the process in its own. Pedagogy as a discipline of education let you make technical decisions. Upper these ones, we find the moral decision. To study the special characteristics of political decisions shows two big mistakes into the controversy «Science-Moral- Politics»: scientism and moral subsunction of Political decision in that. In the last pages, this work goes beyond the causal relation between «meansends ». The authors suggest, for the field of goals, to make subsystem levels for decision making, in stead of ubing the taylorist model in order to organize beveral stages of goals.